Pengaruh Pemberian Ekstrak Bunga Kamboja (Plumeria rubra) Terhadap Fungsi Ginjal Tikus Putih (Rattus Norvegicus) Hiperurisemia Dengan Induksi Potasium Oksonat - Nahdah Aidah (2020)
The kidneys are responsible for 70% of uric acid excretion every day, so an increase in uric acid can affect kidney function. Hyperuricemia can cause kidney hypertension and increase oxidative stress which will cause glomerular damage and tubular ischemia. Frangipani flower extract (Plumeria rubra) contains high amounts of phenols and flavonoids which can prevent the formation of oxidative stress and can reduce uric acid levels. This study aims to determine the effect of frangipani flower extract on kidney function in white rats induced by potassium oxonate. The design of this study was purely experimental using 30 Rattus novergicus rats divided into 5 groups with 6 mice in each group. The control group consisted of group 1 (negative control) and group 2 (positive control with allopurinol). The treatment group consisted of: Groups 3, 4, and 5, which were variations in doses of frangipani flower extract 200, 400, and 600 mg/KgBB /day. The study was conducted for 14 days with the first week of induction and a week later of treatment. Blood samples are taken through the tail to assess uric acid and creatinine levels. The study was analyzed using Kruskall-wallis. The results of significant differences were found at doses of 200, 400 and 600 mg of uric acid levels (p-value 0.004, 0.008 and 0.004) while the mean creatinine differences were found at doses of 200 and 400 mg (p-values 0.004 and 0.042). In this study, a significant decrease in creatinine levels after treatment showed that there was an effect of frangipani flower extract on kidney function with an effective dose of 400 mg/kg/day.